Enhancing polyimide's water barrier properties through addition of functionalized graphene oxide. (14th June 2016) - Hocker, Samuel; Hudson-Smith, Natalie; Schniepp, Hannes C.; Kranbuehl, David E.
Abstract: Graphene oxide produced by Tour's method (GO) and GO functionalized with 4-4′ oxydianiline (ODAGO) are incorporated at 0.01 to 0.10 weight percent (wt%) into a polyimide (PI) made from 3, 3′-benzophenonetetracarboxylic dianhydride (BTDA) and 4-4′ oxydianiline (ODA). The performance properties of these two systems GO-PI and ODAGO-PI at extremely low GO concentrations are compared. ODAGO-PI nanocomposite's performance properties are comparable to previous results citing concentrations 10 times higher and displayed significantly greater improvement than unfunctionalized GO-PI films. The 0.01 wt% ODAGO-PI film demonstrated a factor of ten decrease in water vapor permeability. The 0.10 wt% ODAGO-PI film displayed the maximum increase of 82% in Young's modulus. The water vapor permeability results were fit to the Nielsen law. We found that the model yielded unphysically large aspect ratios for the 0.01 wt% ODAGO-PI, 100 times larger than the AFM-measured value. For the GO-PI, we observe less enhancement of the barrier properties. The large aspect ratio indicates tortuosity effects alone cannot explain the enhanced barrier properties. We propose that the improved barrier properties are also due to a stabilizing effect of the flakes on the polymer matrix, where reduced mobility of the PI chain reduces diffusion through the polymer matrix. ATR-FTIR, WAXS, Raman and Tg results support this view. Graphical abstract: Highlights: Functionalizing graphene oxide shows significant improvements in properties. At less than 0.1 wt%, graphene oxide reduces tenfold polyimide's water permeability. At the molecular level GO decreases chain mobility as well as a tortuosity effect.